Die Register Innocenz' III. 14. Jahrgang (1211/1212). Texte und Indices - Sommerlechner, Andrea (Verlag der Österreichischen Akademie der Wissenschaften, 2018)
The fourteenth volume of the critical edition of pope Innocent III's chancery-registers is containing 161 letters addressed to recipients all over Europe and in the Middle East. In this year of the pontificate, no geographical focus is discernible. However, christianitas as threatened at three frontiers (in Spain and the East by Muslims, in Southern France by heretics) is a topic constantly recurring in the Pope's letters. The register of Innocent's fourteenth year of pontificate is one of the four volumes transmitted not as original but as a copy written at the Curia in mid-14th century and as print published in the 17th century.